PERANCANGAN SISTEM INFORMASI PENGGAJIAN TERKOMPUTERISASI DALAM RANGKA MENINGKATKAN EFEKTIVITAS, EFISIENSI, DAN PENGENDALIAN INTERNAL PADA YAYASAN LAZARIS - ORELIA WIBOWO, IVONE (Universitas Katolik Widya Mandala Surabaya, 2012)
This study uses SMAK St. Louis1 and SMAK St.Louis2 as a pilot project. Payroll system in both schools currently has aweakness in the teacher’s attendance recording system and payroll, data are saved manually. This weaknesses lead to some other payroll constraints which resulted less effective, less efficient, and has a weak internal control payroll system. Research conducted in the form of case studies. Type of data collected is qualitative data derived from the internal organization. Data collection methods are interviews and documentation. The unit of analysis in this study is the procedure, documents, and payroll records. Data analysis technique used is systems analysis, design concepts, and physical design. Research has been conducted, resulting in a computerized payroll information system design in order to improve effectiveness, efficiency, and internal controls on Lazaris Foundation. Computerized payroll information system design includes the design concept consists of system flowcharts, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and physical design consisting of design output, input, databases, and access that results in a payroll application program.